Overeating, caloric restriction and mammographic density in Spanish women. DDM-Spain study. (November 2018) - del Pozo, María del Pilar; Castelló, Adela; Vidal, Carmen; Salas-Trejo, Dolores; Sánchez-Contador, Carmen; Pedraz-Pingarrón, Carmen; Moreo, Pilar; Santamariña, Carmen; Ederra, María; Llobet, Rafael; Vioque, Jesús; Pérez-Gómez, Beatriz; et al.
Highlights: Caloric intake above predicted levels seems to increase mammographic density. For every 20% increase in relative energy intake, mammographic density increased by 5%. Caloric restriction does not appear to affect breast density. Abstract: Objectives: Mammographic density (MD) is a strong risk factor for breast cancer. The present study evaluates the association between relative caloric intake and MD in Spanish women. Study design: We conducted a cross-sectional study in which 3517 women were recruited from seven breast cancer screening centers. MD was measured by an experienced radiologist using craniocaudal mammography and Boyd's semi-quantitative scale. Information was collected through an epidemiological survey. Predicted calories were calculated using linear regression models, including the basal metabolic rate and physical activity as explanatory variables. Overeating and caloric restriction were defined taking into account the 99% confidence interval of the predicted value. Odds ratios (OR) and 95% confidence intervals (95%CI) were estimated using center-specific mixed ordinal logistic regression models, adjusted for age, menopausal status, body mass index, parity, tobacco use, family history of breast cancer, previous biopsies, age at menarche and adherence to a Western diet. Main outcome measure: Mammographic density. Results: Those women with an excessive caloric intake (> 40% above predicted) presented higher MD (OR = 1.41, 95%CI = 0.97–2.03; p = 0.070). For every 20% increase in relative caloric consumption the probability of having higher MD increased by 5% (OR = 1.05, 95%CI = 0.98–1.14; p = 0.178), not observing differences between the categories of explanatory variables. Caloric restriction was not associated with MD in our study. Conclusions: This is the first study exploring the association between MD and the effect of caloric deficit or excessive caloric consumption according to the energy requirements of each woman. Although caloric restriction does not seem to affect breast density, a caloric intake above predicted levels seems to increase this phenotype.